The EXPERIENCES OF THE NDMU PRE-SERVICE TEACHERS DURING THEIR ONLINE TEACHING INTERNSHIP - Bansawan, Ralph; Calunsag, Althea; Benaning, Princess Mae; Ehimplar, Mia Amor; Castillo, Ma. Sophia Dorothy (International Journal of Arts, Sciences and Education, 2022)
Abstract Since the start of the COVID-19 pandemic, schools around the world have closed down to prevent the further spread of the virus. As a result, the rapid urgency to shift to online learning tested the existing infrastructure of schools, the ability to use technology in teaching and learning, and material resources readily available to teachers and students (Adedoyin & Sokyan, 2020). Notre Dame of Marbel University had been recently conducted the internship in virtual set up due to the shift to online teaching. In line with this, the descriptive qualitative research aims to describe the experiences of NDMU pre-service teachers who have undergone the online internship training experiences during the pandemic. Specifically, it aimed to determine advantages and opportunities, challenges, and coping mechanisms of the selected language PSTs during their online internship experiences. Based from the results, the researchers determined that utilization of variety of technology tools in the class, collaboration between the cooperating teacher and the PSTs, experiential teaching experience, and enhancement of the 21st century skills emerged as opportunities during the online internship. On the other hand, interaction in an online environment, technical difficulties, limited resources, and lack of time management emerged as the challenges during the online internship of the PSTs, while modeling strategies, asking assistance from cooperating teacher, being resourceful to the available instructional materials, scheduling as a strategy for managing time emerges as coping mechanisms emerged on the narratives of the PSTs. Given these insights, researchers implicated the fellow and the next pre-service teacher to be dedicated in teaching and embrace the new normal despite the current situation with the aid of technology and media tools for pedagogy. Hence, the institution should also recalibrate the online internship program the recognize the advantage and disadvantages of the online teaching internship.